WORK - LIFE BALANCE AND MENTAL HEALTH: EMOTION ENRICHMENT THROUGH YOGA - Macwan, Manishaben Manibhai; Soni, Niraliben A. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The objective of this exploration is to assess the discoveries of picked examinations on yoga’s restorative impacts & to give a full outline of the advantages of normal “Yoga” practice. As the notoriety of brain body wellness programmes like “Yoga”, it’s critical for health care practitioners to understand the “Yoga” nature & evidence for therapeutic impacts. Resulting to it, this research paper presents yoga’s therapeutic effect information as they are been examined on selected population for different conditions. “Therapeutic yoga” is distinct “Yoga” postures & practices usage for health concerns & instruction at “yogic practices and teachings” to prevent or alleviate structural, emotional, physiological, and spiritual suffering, pain or limitations. According to the findings, “yogic practices” improves muscular strength & body flexibility, promote and develop respiratory & cardiovascular function, also reduces anxiety, stress, depression & chronic pain which improve sleep patterns as well as overall well-being & life quality.